2022
DOI: 10.30880/ijie.2022.14.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Surface Metrology for Process Diagnostic of Ultrasonic Vibration Assisted Grinding

Abstract: The applicationof electroplated diamond in ultrasonic vibration-assisted grinding can be a candidate to replace the manual mirror finishing of the stainless-steel surface and the ability to characterize the tool and work surfaces is important for understanding the tool-work interaction during the grinding process. In this study, an ultrasonic vibration-assisted grinding on stainless steel surface using the electroplated diamond tool is performed for the tool-work surface interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…One of the excellent ways for monitoring many mechanical systems, including machining process is by vibration analysis. Ismail et al [16] showed the effectiveness of vibration signal analysis for condition monitoring of the surface roughness in the deep grinding of stainless steel. Gupta et al [17] developed the robust technique for motor fault diagnosis using signal processing.…”
Section: Introductionmentioning
confidence: 99%
“…One of the excellent ways for monitoring many mechanical systems, including machining process is by vibration analysis. Ismail et al [16] showed the effectiveness of vibration signal analysis for condition monitoring of the surface roughness in the deep grinding of stainless steel. Gupta et al [17] developed the robust technique for motor fault diagnosis using signal processing.…”
Section: Introductionmentioning
confidence: 99%